Axilosubclavian venous thrombosis due to compression in the thoracic outlet - López Chapuis, Daniel; Sánchez, Luis; Valverdu, Martín; Sciuto, Fernando (Cirugía del Uruguay, 1993)
Axilosubc/avian venous thrombosis is a complication of the thoracic strait syndrome which frequently determines chronic venous hypertension sequels. The usual treatment of pedicular decompression by means of axillary resection of the first rib improves symptomatology but does not preven/ those seque/s; it is emphasized that tretment with fibrinolytics would make possible long-term adequate venous permeability.